Urban Green Open Space in Indonesia: A Study of Legal Compliance - Aulia Hidayatul Amali; Asmarani Ramli (Universitas Negeri Semarang, 2027)
In accordance with the provisions set forth in Law Number 26 of 2007 on Spatial Planning, urban spatial planning must include a plan for the provision and utilization of green open spaces covering at least 30% of the city's total area. Green Open Spaces play a crucial role in urban spatial planning and mitigating the environmental impacts caused by urbanization. However, studies regarding the integration of Green Open Spaces and spatial planning policies have not been extensively discussed. The objective of this study is to identify the extent of legal compliance regarding green open spaces in the City of Semarang. The research method employed in this study is empirical legal research, utilizing data collection techniques such as interviews, obeconservations and documentation. Based on the research conducted, it was found that the green open space in Semarang City covers an area of 23,146,701 hectares, or 61.94% of the city's total area. This indicates that the green open space in Semarang City is in compliance with the provisions of Law Number of 2007. Furthermore, this study aims to examine the alignment and availability of green open spaces as well as the implementation of related policies in regional planning documents such as the Regional Spatial Plan and Detailed Spatial Plan. The purpose of this study is to ensure that the Semarang City Government plans to add at least 7,487.4 hectares of public green open space so that public green open space in Semarang City reaches 30%.